Пошаговое объяснение:
1) (1 5/8 + 19/24 - 1 1/12)× х =1
(13/8 + 19/24 - 13/12)× х =1
(39/24 + 19/24 - 26/24)× х =1
32/24 × х =1
4/3 × х =1
х= 3/4
2) (2 23/28 + 1 5/7 - 1 13/14) × х =1
(79/28 + 12/7 - 27/14) × х =1
(79/28 +48/28 - 54/28) × х =1
73/28 × х =1
х= 28/73
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Пошаговое объяснение:
1) (1 5/8 + 19/24 - 1 1/12)× х =1
(13/8 + 19/24 - 13/12)× х =1
(39/24 + 19/24 - 26/24)× х =1
32/24 × х =1
4/3 × х =1
х= 3/4
2) (2 23/28 + 1 5/7 - 1 13/14) × х =1
(79/28 + 12/7 - 27/14) × х =1
(79/28 +48/28 - 54/28) × х =1
73/28 × х =1
х= 28/73